New Trends of Fuzzy Systems: Fintech Applications - Azzini, Antonia; Marrara, Stefania; Topalović, Amir (Fuzzy Logic and Applications, 2019)
In the last years, the term Financial Technology (FinTech) has been adopted by literature to describe a wide range of services, aided by several financial technologies, for enterprises or organizations, which mainly address the improvement of the service quality by using Information Technology (IT) applications.